Four new species of Haplosclerida (Porifera, Demospongiae) from the Aleutian Islands, Alaska - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2013)
Four new species of Haplosclerida are described from the Aleutian Islands, Alaska: Callyspongia mucosa n.sp., Cladocroce infundibulum n. sp., Cladocroce attu n. sp. and Cladocroce kiska n. sp. The new species are described and compared to congeners of the region. This is the northernmost record of the genus Callyspongia and the first record of the subgenus Callyspongia from the North Pacific Ocean. To accommodate Cladocroce kiska in its genus the definition has to be broadened to allow sigmas.